Perancangan Aplikasi Penjadwalan Kuliah Pada Perguruan Tinggi - Marliana Sari; Kadri Yusuf (SNASTIKOM, 2023)
Scheduling lectures in higher education is a complex task because it involves many factors such as room availability, lecturer teaching time, and student needs. Therefore, effective and efficient optimization techniques are needed to solve this scheduling problem. This research was conducted to design an effective and efficient lecture scheduling application using genetic algorithms at diploma and undergraduate levels. By using a genetic algorithm, it is hoped that it can produce a lecture schedule that meets the given requirements and constraints, such as minimizing schedule conflicts, optimizing room use, and maximizing lecturer teaching time. The problems raised from this research can be solved by determining the parameters of the genetic algorithm used in scheduling lectures, determining the factors that need to be considered in scheduling lectures using genetic algorithms, the design can be tested and evaluated to see the performance of the genetic algorithm. Lecture scheduling application built using a genetic algorithm